Movement of Plant Nutrients - Tripti Vashisth; Chris Oswalt (EDIS)
This new two-page document discusses soil-applied and foliar fertilization for citrus trees as well as mobile and immobile nutrients and how they affect the choice of fertilization. Written by Tripti Vashisth and Chris Oswalt, and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1373